2021
DOI: 10.1002/ptr.7270
|View full text |Cite
|
Sign up to set email alerts
|

The anticarcinogenic and anticancer effects of the dietary flavonoid, morin: Current status, challenges, and future perspectives

Abstract: Flavonoids constitute one of the most important classes of polyphenols, which have been found to have a wide range of biological activities such as anticancer effects. A large body of evidence demonstrates that morin as a pleiotropic dietary flavonoid possesses potent anticarcinogenic and anticancer activities with minimal toxicity against normal cells. The present review comprehensively elaborates the molecular mechanisms underlying antitumorigenic and anticancer effects of morin. Morin exerts its anticarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 183 publications
0
14
0
Order By: Relevance
“…One of the main components of various food crops and medicinal plants (such as mulberry, almond, tea, coffee, osage orange, apple, onion, etc. ), morin is a dietary flavanol and is used in traditional medicine for the treatment of various diseases that people suffer from (Gutiérrez et al, 2008; Mottaghi & Abbaszadeh, 2021). It was reported that morin (2′,3,4′,5,7‐pentahydroxyflavone) has anti‐carcinogenic, antioxidant, anti‐inflammatory, antiapoptotic, and protective roles against DNA damage (Celik et al, 2020; Kuzu et al, 2019; Shin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main components of various food crops and medicinal plants (such as mulberry, almond, tea, coffee, osage orange, apple, onion, etc. ), morin is a dietary flavanol and is used in traditional medicine for the treatment of various diseases that people suffer from (Gutiérrez et al, 2008; Mottaghi & Abbaszadeh, 2021). It was reported that morin (2′,3,4′,5,7‐pentahydroxyflavone) has anti‐carcinogenic, antioxidant, anti‐inflammatory, antiapoptotic, and protective roles against DNA damage (Celik et al, 2020; Kuzu et al, 2019; Shin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Morin is a dietary flavonol mainly acquired from the plants of Moraceae family. It has been proven that morin possesses multiple pharmacologic actions, including anti-oxidation, anti-inflammation, anti-cancer, anti-microbe, and anti-diabetes (Kataria et al, 2018;Mottaghi and Abbaszadeh, 2021). In study by Ocete et al (1998), they probed the anti-inflammatory role of morin in TNBS-treated rat colitis.…”
Section: Natural Flavonolsmentioning
confidence: 99%
“…No mortality or abnormal manifestations were found in rats given large doses of morin (about 300–2400 mg/kg) for 13 weeks [ 152 ]. The majority of the glycosylated morin administered orally was not absorbed in the small intestine and flowed into the colon, where it is then metabolized by colonic microorganisms to morin aglycones, which are readily absorbed [ 153 , 154 ].…”
Section: Natural Compoundsmentioning
confidence: 99%